Новые и малоизвестные виды рода Scythris (Lepidoptera, Scythrididae) с Алтая - Синев, С.Ю. (Вестник зоологии, 1993)
A species list based on materials of the Soviet-Finnish 1983. Altai Expedition is given. Two species are described as new: S. mikkolai sp. n. and S. jalavai sp. n.;3 specics are for the first time recorded for the Russian Federation. Type material is deposited in the Zoological Institute, Russian Academy of Sciences (St.-Petersburg), a part of S. jalavai sp. n. paratypes are forwarded to the Zoological Museum, University of Helsinki (Finland).